2017
DOI: 10.21475/poj.10.01.17.292
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Leaf Curl Sudan Virus (TLCSDV) causing leaf curl disease on a new host Amaranthus cruentus L.

Abstract: Amaranthus leaf curl disease symptom was observed in the farmer's field based at Jeddah, Saudi Arabia. This crop used as leafy vegetables in many countries. In this study, a field survey was conducted in April 2014 and naturally infected Amaranthus leaf samples were collected to identify the associated virus with leaf curl disease. The causative agent was transmitted through whiteflies (Bemisia tabaci) from naturally infected leaves to healthy Amaranthus seedlings. The begomovirus infection was identified by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Approximately forty different plant virus diseases have been described on more than thirty plant species in Arabian Peninsula (Al-Shahwan, 2003, Idris et al, 2012, Hosseinzadeh et al, 2014, Sohrab and Daur, 2018a, Sohrab and Daur, 2018b). The association of begomovirus with various crops such as, Amaranthus, Beans, Chili, Corchorus, Cucurbits, Mint, Okra, Pumpkin, Tobacco and Tomato have been reported so far from Arabian peninsula and the associated begomoviruses are known as TYLCV, ToLCOMV, ToLCSDV, ToLCSDV-Om, ChiLCV, OLCOMV, SqLCV, and BDMV-SA (Al-Shahwan et al, 1997, Al-Shahwan et al, 2002, Ghanem et al, 2003, Idris and Brown, 2005, Ajlan et al, 2007, Khan et al, 2008, Khan et al, 2014, Fazeli et al, 2009, Idris et al, 2011, Idris et al, 2012, Idris et al, 2014, Mohamed et al, 2012, Khan et al, 2013a, Khan et al, 2013b, Al-Saleh et al, 2014a, Al-Saleh et al, 2014b, Akhtar et al, 2014, Hosseinzadeh et al, 2014, Sohrab, 2016, Sohrab et al, 2016a, Sohrab et al, 2016b, Sohrab et al, 2016c, Sohrab et al, 2016d, Sohrab et al, 2016e, Sohrab, 2017, Sayed and Sohrab, 2017, Al-Shahwan et al, 2017, Sohrab and Daur, 2018a, Sohrab and Daur, 2018b). In this study, the association of begomovirus infection to tomato disease has been provided based on virus identification, sequencing and genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately forty different plant virus diseases have been described on more than thirty plant species in Arabian Peninsula (Al-Shahwan, 2003, Idris et al, 2012, Hosseinzadeh et al, 2014, Sohrab and Daur, 2018a, Sohrab and Daur, 2018b). The association of begomovirus with various crops such as, Amaranthus, Beans, Chili, Corchorus, Cucurbits, Mint, Okra, Pumpkin, Tobacco and Tomato have been reported so far from Arabian peninsula and the associated begomoviruses are known as TYLCV, ToLCOMV, ToLCSDV, ToLCSDV-Om, ChiLCV, OLCOMV, SqLCV, and BDMV-SA (Al-Shahwan et al, 1997, Al-Shahwan et al, 2002, Ghanem et al, 2003, Idris and Brown, 2005, Ajlan et al, 2007, Khan et al, 2008, Khan et al, 2014, Fazeli et al, 2009, Idris et al, 2011, Idris et al, 2012, Idris et al, 2014, Mohamed et al, 2012, Khan et al, 2013a, Khan et al, 2013b, Al-Saleh et al, 2014a, Al-Saleh et al, 2014b, Akhtar et al, 2014, Hosseinzadeh et al, 2014, Sohrab, 2016, Sohrab et al, 2016a, Sohrab et al, 2016b, Sohrab et al, 2016c, Sohrab et al, 2016d, Sohrab et al, 2016e, Sohrab, 2017, Sayed and Sohrab, 2017, Al-Shahwan et al, 2017, Sohrab and Daur, 2018a, Sohrab and Daur, 2018b). In this study, the association of begomovirus infection to tomato disease has been provided based on virus identification, sequencing and genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic diversity of and variability of TYLCV and Chilli leaf curl virus from Solanaceous crops have been reported earlier from the Kingdom of Saudi Arabia, Arabian Peninsula and South East Asia ( Idris et al, 2012 , Idris et al, 2014 , Khan et al, 2013 , Hosseinzadeh et al, 2014 , Kenyon et al, 2014 ). So far, only a few begomoviruses in the Kingdom such as TYLCV and ToLCSDV causing disease in Tomato, Cucumber, Sponge gourd, Squash, Mentha, Corchorus, Amaranthus, and Okra have been reported ( Idris et al, 2012 , Idris et al, 2014 , Al-Saleh et al, 2014 , Sohrab, 2016 , 2017a , 2017b , Sohrab, 2020 , Sohrab et al, 2016 , Sohrab and Daur, 2018a , 2018b ). The Association of ChiLCV and betasatellite infecting crops has been reported from Oman ( Khan et al, 2013 , Shahid et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The transmission and spread of TYLCV from tomato to Chilli crops shows an alarming situation for vegetable growers in the kingdom of Saudi Arabia. It is well reported that the weeds and whiteflies play an important role as an alternative host and to spread of begomovirus from one region to others with extended hosts range ( Sohrab, 2017a , 2017b , Sohrab, 2020 , Sohrab and Daur, 2018a ). The genetic diversity is a common phenomenon in both plants and humans and favors the emergence of new virus strains/ species and causing diseases in both plants and humans ( Ahmad et al, 2009 , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the occurrence of begomoviruses causing disease in many crops like Amaranthus, Beans, Corchorus, Cucurbits, Okra, Tomato has been reported from Saudi Arabia [9][10][11][12][13][14]. Globally, many viruses infecting mint species have been identified and published [6][7][8].…”
mentioning
confidence: 99%